Quality in academic services of the University of Évora: the implementation of the Common Assessment Framework tool - Nogueiro, Teresa (2012)
It’s urgent to evaluate quality. But we wonder how to evaluate it? Why is it important? The degrees, the courses, the services that support all the University,…What? To evaluate the quality of degrees/courses taught on a Higher Superior Institution it was approved legislation to make compulsory its evaluation. What about the structures that support all the life of a Higher Superior Institution? Shouldn’t their quality also be evaluated? What happens if, for instance, the Academic Services doesn’t work properly or collapse? For each institution to know the weak and strong points, the threats and opportunities of a service, a degree, a course, etc. is a matter of survival. But survival is not enough we must innovate and that is equal to quality. This study presents the various aspects relating to issues of quality, the model Common Assessment Framework, the diagnosis and the main results obtained by the use of questionnaire surveys applied to some students, internal clients and managers of Academic Services of the University of Évora. The main objective of the study was to assess the grade of satisfaction with the quality of service, the performance of all stakeholders, and hence the sustainability of this service. Some strengths, weaknesses and suggestions for continuous improvement are also presented.